Naringenin as a neurotherapeutic agent in Alzheimer’s disease: epigenetic signatures, gut microbiota alterations, and molecular neuroprotection - Lai, Zhenzhen; Ke, Long; Zhao, Wei (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) remains a major neurodegenerative disorder characterized by progressive cognitive decline, amyloid-β (Aβ) aggregation, tau pathology, oxidative stress, and chronic neuroinflammation. In recent years, the dietary flavonoid naringenin, abundant in citrus fruits, has gained attention as a multi-target neuroprotective agent with potential application in AD therapy. Preclinical studies demonstrate that naringenin exhibits robust antioxidant activity, notably through activation of the nuclear factor erythroid 2-related factor 2 (Nrf2)/antioxidant response element (ARE) signaling pathway, which reduces ROS and preserves mitochondrial integrity. Furthermore, naringenin upregulates AMPK-mediated autophagy, aiding in the clearance of toxic Aβ peptides and promoting neuronal survival. Inflammatory cascades are significantly downregulated following naringenin treatment. Additionally, naringenin modulates estrogen receptor and PI3K/Akt signaling, contributing to enhanced neuronal viability and reduced apoptosis. Notably, its ability to inhibit acetylcholinesterase suggests promise for restoring cholinergic neurotransmission. Despite these benefits, naringenin’s poor solubility and limited oral bioavailability hinder clinical translation. To address these challenges, advanced nanocarrier-based delivery systems have been engineered to facilitate blood–brain barrier penetration and sustained brain targeting, markedly improving cognitive outcomes in animal models. Safety profiles in rodents indicate low toxicity at therapeutic doses, reinforcing its viability as a candidate compound. This review highlights the multifaceted mechanisms and delivery strategies of naringenin in AD, and underscores the need for well-designed clinical trials to confirm its efficacy and safety in humans.